Analisis Indikator Makro Ekonomi Terhadap Tingkat Kemiskinan di Provinsi Sumatera Barat - Cempaka Rizki Ambar Sari; Dela Resina; Neng Kamarni (Fakultas Sastra Universitas Ekasakti, 2021)
Poverty is a problem of economic development which is always an interesting discussion. Poverty has an impact on socio-economic burdens, increases in crime, decreases the quality of life, and hinders the creation of superior human resources. The objectives of this study were to 1) analyze the concept and development of poverty in West Sumatra Province; and 2) to analyze the effect of macroeconomic indicators on poverty in West Sumatra Province. The macroeconomic indicators used are Economic Growth Rate based on Gross Regional Domestic Product (GRDP) and Human Development Index (HDI). The analytical tool used is multiple linear regression which includes data from 19 districts and cities in West Sumatra Province during the period 2015-2019. From the results of this study, it was found that in general the poverty rate in West Sumatra Province from 2015-2019 continued to decline. The variable rate of economic growth has a positive relationship with the level of poverty in West Sumatra Province. Meanwhile, the HDI variable has a significant effect on the poverty level and has a negative relationship.